Computable Constants for Korn’s Inequalities on Riemannian Manifolds - Knops, R. J. (Journal of elasticity, 2021)
A method is presented for the explicit construction of the non-dimensional constant occurring in Korn’s inequalities for a bounded two-dimensional Riemannian differentiable simply connected manifold subject to Dirichlet boundary conditions. The method is illustrated by application to the spherical cap and minimal surface.